Tourism Inflow and Economic Growth in South Africa: The Role of Digital Inclusion - Oladunjoye, Opeyemi Nathaniel; Chaka, Mpho (International Journal of Economics and Financial Issues, 2025)
The importance of digital inclusion in promoting economic growth remains widely debated, particularly in the light of its impact on the framework of tourism-economic growth. Growing support from the government, legislators, and civil society in South Africa highlights how vital it is to address digital inequality through inclusive digital efforts. Nevertheless, there is still a lack of empirical data assessing how digital inclusion affects the relationship between tourism and economic expansion in South Africa. The neoclassical growth theory, which emphasizes technology as a crucial component of economic progress, serves as the foundation for this study. It also incorporates the tourist-led growth hypothesis, which emphasizes tourism as a major driver of economic performance. The results show that labour force participation and gross fixed capital formation have a major impact on South Africa’s economic growth, but trade openness, the interaction of digital inclusion and tourism, and tourism inflows do not seem to be the main drivers of economic growth in South Africa. The study concludes that the synergy between tourism and digital inclusion currently lacks a substantial impact on economic growth. As a policy response, the study advocates for streamlined visa procedures, improved security and infrastructure to support sustained tourist arrivals, and a comprehensive national strategy to expand internet access, develop digital infrastructure, and enhance digital literacy, particularly in historically marginalized rural communities with high tourism potential.